The Influence of Using Tiktok Social Media Towards Students' Learning Outcomes In Thematic Learning At Grade III of SD Negeri 01 Ulak Karang Selatan - Lesma wati; Nofriza Efendi; Yona Syaida Oktira; Ayunis Ayunis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research aims to determine whether there is an influence of the use of TikTok social media on student learning outcomes in thematic learning in Class III of SD Negeri 01 Ulak Karang Selatan. This research was based on several students who were influenced by TikTok social media, for example when their friends asked other friends questions such as: asking for assignments with the words